2007
DOI: 10.1590/s0100-879x2007000400019
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1 alleles in juvenile-onset systemic lupus erythematosus: renal histologic class correlations

Abstract: Human leukocyte antigens (HLA) DRB1*03 and DRB1*02 have been associated with systemic lupus erythematosus (SLE) in Caucasians and black populations. It has been observed that certain HLA alleles show stronger associations with SLE autoantibodies and clinical subsets, although they have rarely been associated with lupus renal histologic class. In the present study, HLA-DRB1 allele correlations with clinical features, autoantibodies and renal histologic class were analyzed in a cohort of racially mixed Brazilian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
(37 reference statements)
2
18
0
Order By: Relevance
“…Our findings are in harmony with the results reported by Liphaus et al (2007), who did not find significant relation between HLA-DRB1 alleles and nephritis musculoskeletal, cutaneous, neuropsychiatric, Hematologic, pulmonary or cardiac involvement in Brazilian children with SLE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in harmony with the results reported by Liphaus et al (2007), who did not find significant relation between HLA-DRB1 alleles and nephritis musculoskeletal, cutaneous, neuropsychiatric, Hematologic, pulmonary or cardiac involvement in Brazilian children with SLE.…”
Section: Discussionsupporting
confidence: 92%
“…In a cohort of Brazilian juvenile onset SLE patients; Liphaus et al (2007) reported that HLA-DRB1 alleles were not related to the occurrence of LN, but they found that HLA-DRB1*17, HLA-DRB1*10, HLA-DRB1*15 and HLA-DRB1*07 alleles were significantly higher in patients with renal histologic class I, IIA, IIB and V, respectively. We believe that differences in the results of these studies can be explained by either the effect of ethnicity and or differences in numbers of the studied subjects.…”
Section: Discussionmentioning
confidence: 97%
“…(22) Interestingly, we found increased frequencies in SLE patients between HLA DRB3, DRB1*11 and serositis, skin manifestations and HLA DQB1*3, nephritis and HLA DRB1*15, while hematological manifestations were associated with HLA DRB1*10 and central nervous system involvement and HLA DRB1*11. Liphaus et al found that renal involvement is associated with DRB1*15 among a Brazilian population (23) and El Sherbini found no relation between DRB1*15 and renal involvement, (15) while in a similar but larger scale study, Vasconcelos et al found in a Portuguese population that HLADRB1 * 08 allele frequency was increased among SLE patients with neurological involvement. (24) …”
Section: Discussionmentioning
confidence: 96%
“…The major histocompatibility complex (MHC) genotype determines which MHC molecules are available to the antigens and thus how well the antigens can be recognized by T cells. Particular MHC genes have been associated with an increased risk of an immune response to self-antigens and hence an increased risk of disease development, such as that observed in SLE patients 3,16,17…”
Section: Introductionmentioning
confidence: 99%